The effect of students of sports management and coaching education department on entrepreneurial tendencies of career plans - Mustafa Vural; Yaşar Çoruh (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study investigated the effect of career planning of the students in the Ağrı Ibrahim Çeçen University department of sports management and the coaching education department on entrepreneurial tendencies. The research group consisted of 161 students who studying in Ağrı Ibrahim Çeçen University Sports Management and Coaching Department. In the study, "Personal Career Planning Scale", which was developed by a researcher "Entrepreneurial Tendency Scale", which was developed by another researcher and "Personal Information Form", which was prepared by the researcher was used as a data collection tool. Spearman Correlation (r) coefficient technique was used to reveal the relationship between the career planning sub-dimensions and the entrepreneurial tendencies of the students. The effect between dependent and independent variables of the study was tested by regression analysis. In the correlation analysis performed at the end of the study, it was found that there was a positive relationship between all sub-dimensions of career planning scale and there was a positive and moderate relationship between the career planning and sub-dimensions and entrepreneurial tendencies. As a result of the regression analysis, the sub-dimension of defining opportunities and planning sub-dimension from the career planning has significantly affected the entrepreneurship and it explains 41% of the changes in entrepreneurship. It is possible to say that the participants who have the opportunities and have a plan are more entrepreneurs.